Bohaterowie optymalnie niemożliwi. Geneza, struktura i funkcje mitycznej kontrintuicyjności = Optimally impossible heroes. Genesis, structure and functions of the mythical contrintuitiveness - Czeremski, Maciej (Zielona Góra: Lubuskie Towarzystwo Naukowe)
Mythical heroes always cross the borders of what we think as the everyday condition of the real human being. The object of this research is the explanation of this phenomena by referring to some of the definitions from the cognitivist religious studies and particularly to the idea of contrintuitiveness crucial for this attempt. According to the assumed perspective, the mythical deformation of the concept of human being does not have the accidental character and is limited solely to the infringement of the intuitive expectation connected with ontological categories.
Keywords: mit; kognitywistyka; religioznawstwo kognitywne; kontrintuicyjność; intencjonalny agens; myth; cognitive science; cognitive study of religion; contrintuitiveness; intentional agent